Registration of 'CP 09‐4153', 'CPCL 09‐4160', and 'CP 09‐4758' Sugarcane for Sand Soils in Florida. Issue 3 (1st September 2019) - Singh, Maninder P.; Edmé, S.; Zhao, Duli; Comstock, Jack C.; Davidson, R. Wayne; Gordon, Vanessa S.; Sandhu, Hardev S.; McCord, Per; Sood, Sushma; Baltazar, Miguel
Abstract : 'CP 09‐4153' (Reg. no. CV‐189, PI 688442), 'CPCL 09‐4160' (Reg. no. CV‐188, PI 688443), and 'CP 09‐4758' (Reg. no. CV‐190, PI 688444) are new sugarcane (complex hybrids of Saccharum spp.) cultivars developed through cooperative research conducted by the USDA‐ARS, the University of Florida, and the Florida Sugar Cane League and released to be cultivated on mineral (sand) soils in Florida. Female and male parents, respectively are CPCL 97‐0393 and CPCL 02‐8021 for CP 09‐4153; 'CP 80‐1743' and Poly 01‐8 (a pollen mix) for CPCL 09‐4160; and CP 97‐2103 and CP 92‐1167 for CP 09‐4758. Averaged across three crop cycles, CP 09‐4153 and CP 09‐4758 had, respectively, 32.4 and 21.9% higher cane yield and 28.1 and 20.2% higher sucrose yield compared with 'CL 88‐4730', a commercial reference cultivar. CPCL 09‐4160 did not differ significantly from CL 88‐4730 in cane and sucrose yields, but it was resistant to major sugarcane diseases in the region except ratoon stunt. CP 09‐4153 and CP 09‐4758 were considered to have low to moderate freeze tolerance while CPCL 09‐4160 was considered to be moderate in freeze tolerance. Overall, these three cultivars were released by the Florida Sugarcane Variety Committee due to their high cane and sucrose yields, particularly in the ratoon crops, and their acceptable levels of resistance to brown rust, orange rust (except CP 09‐4758), smut, leaf scald (except CP 09‐4758), Sugarcane mosaic virus strain E, ratoon stunt (except CPCL 09‐4160), and Sugarcane yellow leaf virus .